Evaluation of anti-diabetic prescriptions at Tripura medical college and Dr. BRAM teaching hospital: a cross- sectional study - Das, Lakshman; Debnath, Shubhaleena; Bhattacharjee, Prithul (International Journal of Research in Medical Sciences, 2018)
Background: Diabetes mellitus (DM) is a chronic disease which requires lifelong treatment. The management of type 1 DM depends mainly on insulin, whereas the oral anti-diabetic drugs (OADs) are the first line treatment for type 2 DM. Rational use of the drugs in populations can be effectively studied by analysing the prescription pattern. As there are limited numbers of studies carried out on drug utilization in diabetic patients in North Eastern region of India, authors planned to carry out this study in a tertiary care set up of this region. Methods: A cross-sectional study was carried out in Medicine OPD of Tripura Medical College and Dr. BRAM Teaching Hospital for a period of two months with the objectives of prescription pattern evaluation and the cost of anti-diabetic agents. Drug use pattern of antidiabetics, WHO core prescribing indicators and percentage of cost variation were analysed. Results: A total of 120 prescriptions were analysed during the study period. Metformin was the most commonly prescribed drug. The average cost of therapy per prescription per week was Rs. 94.54. Only 19.43% of the antidiabetics were prescribed from the essential drug list. Conclusions: The cost of prescription can be reduced by choosing the generic drugs without changing its quality and also by choosing drugs from essential drug list.